(untitled) (Third Sector Social Economic Review, 2025)
The allocation of limited assets by accepting bids from competing bidders to determine the sales price mechanism is called “auction”. These assets may consist not only of goods and services but also of real estate, timber rights, antiques, bonds, artworks, oil extraction rights, tax collection rights and even an imperial throne. The main subject that is studied in the field of auction theory is the investigation of bidder behavior and how the auction rules affect the bids. Auction theory is considered a unique field with William Vickrey’s contributions in his paper published in (1961). Vickrey introduced how to calculate the bid, which has the highest expected profit for bidders in first-price sealed-bid auctions. This method, which would later became known as “Vickrey’s Nash equilibrium”, has been the subject of various economic experiments. It is frequently reported in literature that people bid above this equilibrium (overbidding). Researchers tried to explain this anomaly with different approaches like “risk aversion” or “anticipated regret”. The subject of this paper is to explain this anomaly with the modern subfield of game theory called “epistemic game theory”. In this paper we showed that when people bid in an auction game, they don’t bid according to Vickrey’s Nash equilibrium, their bidding behavior is more consistent with utility proportional beliefs method which is a solution concept developed by epistemic game theorists.